A histopathological study of skin biopsy specimens in a tertiary care hospital with a keynote on clinicopathological correlation - George, Varughese Padinjattadathu; S, Sowmya; S, Krishnan (Annals of Pathology and Laboratory Medicine, 2020)
Introduction: The prevalence of dermatological lesions is notably high among tropical countries and the spectrum varies significantly with geographical distribution and co-existing disorders leading to many differential diagnoses. A histopathological examination is essential to arrive at a final diagnosis, which paves way for clinicopathological correlation. Materials and Methods: This is an observational study over a period of 10 years in the Department of Pathology at a rural area based tertiary care hospital. Histopathological analysis of 800 skin biopsy specimens was done and slides were stained with hematoxylin and eosin stains with the application of special stains such as Fite-Faraco and Ziehl–Neelsen stains and immunohistochemical stains such as S100 in warranted cases. The data obtained were tabulated and analyzed for clinicopathological correlation. Results: Among 800 cases analyzed, specific histopathological diagnosis was made in 87.9% of cases. Neoplastic skin lesions were seen in 22.4% of cases, whereas 77.6% of cases were non-neoplastic. Leprosy was found to be the most common skin lesion. Clinicopathological correlation showed concordance in 430 cases (54%) with significant correlation in leprosy and malignant melanocytic skin tumors. Conclusion: Granulomatous inflammation is still rampant with leprosy and tuberculosis as the leading causes in spite of extensive programmes and preventive measures. In cases where skin biopsy delivered a non-specific diagnosis, infective or neoplastic etiology was ruled out. The heterogeneity in the clinical presentation of skin diseases makes histopathological examination a gold standard tool to establish both the final diagnosis and clinicopathological correlation.